Effect of Change in Surplus Ratio, Incurred Loss Ratio, Liquidity Ratio, Premium Growth Ratio, Firm Size and Risk Based Capital to Predict The Posibilities of Financial Distress : The Case of Indonesian Non-Life Insurance Listed in Indonesia Insurance Dir - Dewi, Tiara Trie Chandra; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2016)
The insurance company has different characteristics with other companies, so that performance appraisal of insurance company use specific ratios created by The National Association of Insurance Commissioners (NAIC). This study aims to examine the effect of financial ratios of insurance company, namely change in surplus ratio, incurred loss ratio, liquidity ratio, premium growth, firm size and risk based capital (RBC) to forecast the possibility of financial distress, a deteriorating financial condition prior to the bankruptcy of non-life insurance companies registered in Indonesia Insurance Directory in period 2010-2014. The insurance companies which experiencing financial distress is determined based on negative net profit for two consecutive years. By using purposive sampling obtained 63 samples of insurance companies, 53 companies experiencing non-financial distress, 10 companies experiencing financial distress. The method used in this study using logistic regression. The result indicates that the variable of incurred loss ratio, liquidity (liabilities to liquid asset) ratio are positive and significant effect on the occurrence of financial distress. Firm size variable has a negative and significant effect on the occurrence of financial distress, while change in surplus ratio, premium growth ratio and risk based capital have no significant effect on the insurance company’s financial distress.